Wind effect on gyrotactic micro-organism surfacing in free-surface turbulence. (July 2019) - Mashayekhpour, Maryam; Marchioli, Cristian; Lovecchio, Salvatore; Lay, Ebrahim Nemati; Soldati, Alfredo
Highlights: Applicability of EL point-particle approach to gyrotactic swimmer dynamics in wind-sheared free-surface turbulence. Simulations with turbulence and swimmer dynamics based on LPT in DNS flow fields. Phenomenology of gyrotaxis-biased surfacing of swimmers in free-surface turbulence. Abstract: We examine the effect of wind-induced shear on the orientation and distribution of motile micro-swimmers in free-surface turbulence. Winds blowing above the air–water interface can influence the distribution and productivity of motile organisms via the shear generated just below the surface. Swimmer dynamics depend not only on the advection of the fluid but also on external stimuli like nutrient concentration, light, gravity, which are in turn coupled to and influenced by the distribution of the swimmers. Here we focus on gyrotaxis, resulting from the gravitational torque generated by an asymmetric mass distribution within the organism. The combination of such torque with the viscous torque due to shear can reorient swimmers, reducing their vertical migration and causing entrapment in horizontal fluid layers. Through DNS-based Euler–Lagrangian simulations we investigate the effect of wind-induced shear on the motion of gyrotactic swimmers in turbulent open channel flow. We consider different wind forcing and swimmers with different reorientation time (reflecting the ability to react to turbulent fluctuations). We show that only stable (high-gyrotaxis) swimmers may reach the surface and form densely concentrated filaments, the topology of which depends on the wind direction. Otherwise swimmers exhibit weaker vertical fluxes and loose segregation at the surface.